Psychometric properties of conflict monitoring and conflict adaptation indices: Response time and conflict N2 event‐related potentials. (29th August 2013) - Clayson, Peter E.; Larson, Michael J.
Abstract: We assessed the psychometric properties, including internal consistency, test‐retest reliability, and number of trials needed for stability, for response time (RT) and conflict N2 amplitude measures of conflict adaptation (i.e., sequential trial or Gratton effects). Event‐related potentials (ERPs) were obtained from 79 healthy individuals (44 female) during completion of a modified Eriksen flanker task. RTs and N2 amplitude showed reliable conflict adaptation (i.e., previous‐trial congruency influenced current‐trial measures). Conflict adaptation indices were stable as indicated by reliable internal consistency and 2‐week test‐retest stability. The number of trials needed for conservative, reliable RT and N2 amplitude measurements was 29 and 30, respectively. This investigation empirically establishes that these conflict adaptation indices represent robust, dependable measures.